Autism Therapies in Nepal: A Review of Available Interventions, Effectiveness Evidence, Accessibility Barriers, and Research Gaps - Khanal, Pooja; Dawadi, Anushka; Shrestha, Lisha Khambu; Shrestha, Ninu; Shrestha, Menuka; Chaudhary, Narayan Prasad; Maskey, Avas Man; Dhakal, Deepa; Khanal, Ashish; Giri, Suja (Journal of Multidisciplinary Research Advancements, 2026)
Autism Spectrum Disorder (ASD) affects approximately 1 in 100 children globally, yet in Nepal, awareness is limited, diagnosis is delayed, and therapy access is severely constrained. This review synthesises literature on autism therapies in Nepal from 2014 to 2026. Findings reveal diverse documented interventions—pharmacological, occupational, physical, speech, psychological, yoga-based, vision therapy, and augmentative and alternative communication (AAC)—but no randomised controlled trials have been conducted in Nepal. Accessibility barriers are severe: services concentrate in Kathmandu; workforce shortages leave districts without therapists; the monthly disability allowance is insufficient; and no national autism strategy exists. AAC remains primarily low-tech. Urgent action is needed, including prevalence studies, RCTs of culturally adapted interventions, service extension beyond urban centres, and a national autism strategy.